Hypoglycemic Potential of Aqueous Extract of Moringa oleifera Leaf and In Vivo GC-MS Metabolomics - Khan, Washim; Parveen, Rabea; Chester, Karishma; Parveen, Shabana; Ahmad, Sayeed (Frontiers in Pharmacology, 2017)
Moringa oleifera Lam. (family; Moringaceae), commonly known as drumstick, have been used for centuries as a part of the Ayurvedic system for several diseases without having any scientific data. Demineralized water was used to prepare aqueous extract by maceration for 24 h and complete metabolic profiling was performed using GC-MS and HPLC. Hypoglycemic properties of extract have been tested on carbohydrate digesting enzyme activity, yeast cell uptake, muscle glucose uptake and intestinal glucose absorption. Type 2 diabetes was induced by feeding HFD for 8 weeks and a single injection of streptozotocin (STZ, 45 mg/kg body weight, intraperitoneally) was used for the induction of Type 1 diabetes. Aqueous extract of M. oleifera leaf was given orally at a dose of 100 mg/kg to STZ induced rats and 200 mg/kg in HFD mice for 3 weeks after diabetes induction. Aqueous extract remarkably inhibited the activity of α-amylase and α-glucosidase and it displayed improved antioxidant capacity, glucose tolerance and rate of glucose uptake in yeast cell. In STZ induced diabetic rats, it produces a maximum fall up to 47.86% in acute effect whereas in chronic effect, it was 44.5% as compared to control. The fasting blood glucose (FBG), lipid profile, liver marker enzyme level were significantly (P<0.05) restored in both HFD and STZ experimental model. Multivariate principal component analysis (PCA) on polar and lipophilic metabolites revealed clear distinctions in the metabolite pattern in extract and in blood after its oral administration. Thus, the aqueous extract can be used as phytopharmaceuticals for the management of diabetes by using as adjuvants or alone.